A single mutation that increases maize seed weight. - Giroux, M J (1996)
The maize endosperm-specific gene shrunken2 (Sh2) encodes the large subunit of the heterotetrameric starch synthetic enzyme adenosine diphosphoglucose pyrophosphorylase (AGP; EC 2.7.7.27). Here we exploit an in vivo, site-specific mutagenesis system to create short insertion mutations in a region of the gene known to be involved in the allosteric regulation of AGP. The site-specific mutagen is the transposable element dissociation (Ds). Approximately one-third (8 of 23) of the germinal revertants sequenced restored the wild-type sequence, whereas the remaining revertants contained insertions of 3 or 6 bp. All revertants retained the original reading frame 3' to the insertion site and involved the addition of tyrosine and/or serine. Each insertion revertant reduced total AGP activity and the amount of the SH2 protein. The revertant containing additional tyrosine and serine residues increased seed weight 11-18% without increasing or decreasing the percentage of starch. Other insertion revertants lacking an additional serine reduced seed weight. Reduced sensitivity to phosphate, a long-known inhibitor of AGP, was found in the high seed-weight revertant. This alteration is likely universally important since insertion of tyrosine and serine in the potato large subunit of AGP at the comparable position and expression in Escherichia coli also led to a phosphate-insensitive enzyme. These results show that single gene mutations giving rise to increased seed weight, and therefore perhaps yield, are clearly possible in a plant with a long history of intensive and successful breeding efforts.